2023
DOI: 10.1002/ese3.1436
|View full text |Cite
|
Sign up to set email alerts
|

Failure characteristic and acoustic emission spatio‐temporal evolution of coal under different cyclic loading rates

Abstract: The coal and rock dynamic disasters occur more and more frequently in deep mining, which is tightly correlated to the instability of coal pillars under high stress and cyclic disturbance load. In this study, the strength, deformation behaviors, and failure mechanism of coal under cyclic loading in a high-stress state were investigated by considering the influence of cyclic loading rate. The experimental results indicate that the compressive strength is positively correlated with the cyclic loading rate, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…A higher b value will be obtained if most events are small events with less energy, indicating less cracks or cracks growing slowly, whereas a lower b value represents most AE events that are large events with high energy, indicating many cracks or cracks growing fast. A undulate b value meaning unstable cracks expand [6,33], so the b value is related with the damage degree closely.…”
Section: Characteristic Of Acoustic Emission Parameters In Thementioning
confidence: 99%
See 1 more Smart Citation
“…A higher b value will be obtained if most events are small events with less energy, indicating less cracks or cracks growing slowly, whereas a lower b value represents most AE events that are large events with high energy, indicating many cracks or cracks growing fast. A undulate b value meaning unstable cracks expand [6,33], so the b value is related with the damage degree closely.…”
Section: Characteristic Of Acoustic Emission Parameters In Thementioning
confidence: 99%
“…The energy evolution plays an important role in explaining the mechanism of rock engineering disasters. The energy input by the loading machine can transform and release in multiple forms, such as elastic deformation, plastic deformation [6], infrared heat radiation, elastic wave, and electric energy. The initiation and expansion of microcracks will cause energy release in the form of acoustic emission (AE), which has been used for the prediction of quantitative rock damage widely [7].…”
Section: Introductionmentioning
confidence: 99%
“…Wang performed uniaxial cyclic compression tests at different frequencies on coal samples and observed that the elastic modulus of coal exhibited an initial sharp increase followed by a subsequent sharp decrease with increasing number of cyclic loading cycles [5]. Liu investigated the mechanical and failure characteristics of coal subjected to cyclic load under high stress and discovered a positive correlation between compressive strength of specimens and cyclic loading rate, as well as identified tensile failure as the microfailure mechanism during cyclic loading [6]. Vaneghi determined that higher load amplitudes resulted in greater degrees of strength degradation in hard rock, while also observing more localized fractures compared to static loading conditions [7].…”
Section: Introductionmentioning
confidence: 99%